Levantamento de seio maxilar em coelhos utilizando vitrocerâmica bioativa particulada (Biosilicato®): análise microscópica imunohistoquímica - Thompson, Francis Cazelli (2016)
Maxillary sinus lift is a valuable procedure in the rehabilitation of atrophic maxilla. The autogenous graft is considered the gold standard in bone repair, however, it is an invasive procedure and a limited amount of material is available. In this way, the use of biomaterials becomes an interesting alternative. This was the objective of the evaluation of the bioactive behavior of bioactive glass-ceramic (Biosilicate®) particulate as a filling material for maxillary sinus removal of rabbits, associated or not with crushed autogenous bone graft compared to deproteinized bovine bone (Bio-Oss®). 45 animals were distributed in five groups according to the type of filling material of the maxillary sinuses and euthanized after 15, 45 and 90 days. An analysis of the biological mechanisms involved in the repair process, obtained by histomorphometry and immunohistochemistry, through the expression of Runx-2 and VEGF. The results presented higher rates of bone neoformation in the groups with Bio-Oss® associated to the autogenous bone in the period of 45 days, while the smaller ones that were found in the period of 15 days for the group that associated the Biosilicato® to the autogenous bone, however, no statistical difference in the therapeutic periods was found. Immunohistochemical analysis showed similar levels of markup to RUNX-2 and VEGF in 45 days. In the period of 90 days RUNX-2 for marking Biosilicate® was only moderate, while VEGF levels marking Biosilicate® containing groups were lower than those filled with Bio-Oss ®. The combination with autologous bone appeared to improve Biosilicate® properties, however, bovine hydroxyapatite showed the best levels of osteogenic activity.